PENGARUH PERSONAL SELLING DAN ADVERTISING TERHADAP KEPUTUSAN PEMBELIAN POLIS PADA NASABAH LIFE AGENCY CHUBB LIFE SURABAYA - administrator administrator; Triana Rista Gessong; Subijanto Subijanto; Ruddy Winarko (Prodi Magister Manajemen Universitas Wijaya Putra, 2019)
The study aims to describe personal selling and advertising partially and simultaneously have effect onpurchase policy insurance of Chubb Life Surabaya. The population in this research is costumers of LifeAgency Chubb Life Surabaya who bought the policy from July to December 2017 totaling 141 people.Sampling in this study using probability sampling technique, namely proportionate stratified randomsampling is determined by the formula slovin so that the number of samples is 104 people hereinaftercalled respondent. Data analysis techniques using multiple and partial correlation analysis throughSPSS program tools and descriptive analysis techniques. The result of the analysis shows that personalselling and advertising simultaneously have effect on purchase policy insurance of Chubb Life Surabaya.personal selling and advertising partially effect on purchase policy insurance of Chubb Life Surabaya.The value of R2 = 0.372 which means that 37.2% purchase decision of Chubb Life insurance policy cabeaffected by personal selling and advertising, while the remaining 62.8% is influenced by other variablesoutside of personal selling and advertising.Keywords: purchase decision, personal selling, advertising